2018
DOI: 10.1111/apt.14606
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: association between acetaminophen and nonsteroidal anti‐inflammatory drugs (NSAIDs) and risk of Crohn's disease and ulcerative colitis exacerbation

Abstract: Contrary to generally accepted belief, we did not find a consistent association between NSAIDs use and risk of CD and UC exacerbation. There was also no consistent evidence for association with acetaminophen although further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 57 publications
(186 reference statements)
0
30
0
1
Order By: Relevance
“…Unlike COX-1, which is constitutively expressed in multiple tissues, including the gastrointestinal tract, the expression of COX-2 is typically induced by inflammation, such as TNF stimulation [ 14 , 15 ]. Additionally, COX-2 inhibitor treatment of UC patients has for a long time been linked with an increased risk of flaring disease [ 16 , 17 ], although a recently published meta-analysis has questioned this generalization in patients with IBD [ 18 ]. Further, the most abundant COX-derived metabolite [ 15 ], PGE 2 , has been shown to be required for intestinal wound repair by promoting the differentiation of wound-associated epithelial cells (WAE) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike COX-1, which is constitutively expressed in multiple tissues, including the gastrointestinal tract, the expression of COX-2 is typically induced by inflammation, such as TNF stimulation [ 14 , 15 ]. Additionally, COX-2 inhibitor treatment of UC patients has for a long time been linked with an increased risk of flaring disease [ 16 , 17 ], although a recently published meta-analysis has questioned this generalization in patients with IBD [ 18 ]. Further, the most abundant COX-derived metabolite [ 15 ], PGE 2 , has been shown to be required for intestinal wound repair by promoting the differentiation of wound-associated epithelial cells (WAE) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the substantial heterogeneity across the 18 studies, this systematic review concluded that both COX-2 and non-selective COX inhibitors appeared safe in IBD patients and should not be withheld. 36 In summary, current evidence consistently demonstrates the safety of COX-2 inhibitors in IBD, especially when used in the short term, up to 3 months. Despite early case reports suggesting potential for harm, meta-analyses have not demonstrated risk of disease flare even with nonselective NSAIDs, although results are drawn from heterogenous studies.…”
Section: Nsaids and Cox-2 Inhibitorsmentioning
confidence: 82%
“…Despite the substantial heterogeneity across the 18 studies, this systematic review concluded that both COX-2 and non-selective COX inhibitors appeared safe in IBD patients and should not be withheld. 36 …”
Section: Nsaids and Cox-2 Inhibitorsmentioning
confidence: 99%
“…Patients with IBD-associated SpA are commonly treated with physical therapy and NSAIDs to relieve pain, swelling, and stiffness. Frequently used with success by rheumatologists, NSAIDs represent a very controversial option for IBD patients [20,21] as that they have been accused of inducing increased rate of flares, hospitalization, and complications [22,23], which are not found in a recent meta-analysis [24]. Therefore, NSAIDS should be used in the short term [25], or COX-2 inhibitors are an alternative option, as less negative data exist [26,27], or paracetamol in case of residual pain or only minimal inflammation.…”
Section: Treatment Of Arthropathies With Conventional Disease-modifyimentioning
confidence: 99%